2003
DOI: 10.1038/sj.ejcn.1601528
|View full text |Cite
|
Sign up to set email alerts
|

Gender, age, socio-demographic and lifestyle factors associated with major dietary patterns in the Spanish Project SUN (Seguimiento Universidad de Navarra)

Abstract: Objective: To ascertain the major dietary patterns in the cohort 'SUN' and to assess the association of several sociodemographic (including age and gender) and lifestyle variables with the adherence to these dietary patterns. Design: This study is a cross-sectional analysis of 3847 subjects (1587 men and 2260 women) belonging to a prospective cohort study based on self-reported questionnaires. A factor analysis based on 30 predefined food groups was conducted to ascertain the major dietary patterns in the coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

38
108
4
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 28 publications
(28 reference statements)
38
108
4
6
Order By: Relevance
“…This finding is consistent with a previous report of our group assessing 3847 university graduates (21) . Adherence to a Western diet (WDP) was associated with the consumption of several kinds of beverages such as sugar-sweetened soft drinks and Adjusted for age (years), gender, energy intake (MJ/d), BMI (four categories), physical activity during leisure time (quartiles, MET-h/week), smoking (six categories), marital status (four categories) and several diseases (CVD, cancer and ulcer).…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with a previous report of our group assessing 3847 university graduates (21) . Adherence to a Western diet (WDP) was associated with the consumption of several kinds of beverages such as sugar-sweetened soft drinks and Adjusted for age (years), gender, energy intake (MJ/d), BMI (four categories), physical activity during leisure time (quartiles, MET-h/week), smoking (six categories), marital status (four categories) and several diseases (CVD, cancer and ulcer).…”
Section: Discussionsupporting
confidence: 94%
“…Hu et al (36) in a large study in US men reported that individuals who had higher scores for a 'Western' dietary pattern were more likely to have lower levels of income and education. Our results of the dual pattern are similar to those of previous studies, in which patterns with high loadings in fruit and vegetables were frequently positively associated with age (33,39,40) , higher income, higher educational levels (41) or higher socio-economic status, sometimes in a genderspecific manner. Cai et al (39) , in Shanghai, reported that more educated people had higher scores for all three patterns retained.…”
Section: Discussionsupporting
confidence: 90%
“…However, dietary factor scores of both patterns were comparable for individuals with FHO þ and FHOÀ. However, it should be noted that in comparison to the study of Sanchez-Villegas et al, 43 which reported results stratified on the basis of gender, men and women were studied together in this study. On the other hand, this study also suggests that individuals having an FHO þ and having a high score of Western pattern are more likely to be obese.…”
Section: Discussionmentioning
confidence: 63%
“…In the literature, Sanchez-Villegas et al 43 reported that women with a personal history of obesity are less likely to follow a Western pattern and men with a personal history of obesity are more likely to follow a healthy pattern (SpanishMediterranean). Thus, it is reasonable to believe that the presence of obesity or an FHO þ can also have an influence on adherence to dietary patterns.…”
Section: Discussionmentioning
confidence: 99%